EFFECTIVENESS OF PERINEAL PROTECTION DEVICES IN REDUCING BIRTH-RELATED PERINEAL TRAUMA IN PRIMIPAROUS WOMEN: A SYSTEMATIC REVIEW AND META-ANALYSIS - Saidova Zuhra Shuhrat qizi; Tursoatova Shaxlo Muhiddin qizi; Zakirova Nodira Islamovna (GLOBAL SCIENTIFIC RESEARCH AND INTELLECTUAL PURSUITS, 2025)
Perineal trauma during vaginal birth remains a prevalent issue among primiparous women, often leading to postpartum pain, sexual dysfunction, and long-term complications. This thesis evaluates the effectiveness of perineal protection devices (PPDs) in reducing birth-related perineal trauma through a systematic review and meta-analysis of recent randomized controlled trials (RCTs). Drawing on data from five RCTs involving 2,331 participants, primarily from 2023–2025 studies, PPD usage significantly increased intact perineum rates (RR 1.41; 95% CI 1.18–1.69; p < 0.001) without adverse neonatal effects. Sensitivity analyses further highlighted reductions in labial tears (RR 0.72; p=0.02). These findings underscore PPDs' role in enhancing maternal outcomes amid rising global cesarean rates and emphasis on vaginal birth safety. Recommendations advocate for broader clinical integration, supported by emerging high-quality evidence, to address disparities in maternal health.